Efeito da microestrutura prévia nas propriedades mecânicas de um aço bifásico com requisito de expansão de furo - Marcus Vinicius Pereira Arruda (2019)
The purpose of this study was to evaluate the effect of the previous hot rolled microstructure on the microstructure and final mechanical properties of a cold rolled Dual Phase 980 MPa steel grade with hole expansion (HE) requirement. Samples with different initial microstructures, one of them consisting predominantly of ferrite, bainite and martensite (FBM) and the other by ferrite and pearlite (PF), were cold rolled on a laboratory mill and submitted to continuous annealing cycles at Gleeble and dilatometer simulators. The treated specimens were submitted to tensile and HE tests and microstructural characterization by scanning electron microscope (SEM), EBSD and nanohardness. In general, the FBM microstructure showed higher values of TS and YS and lower EL than samples from FP microstructure. This result was attributed to the higher amount of second phase (bainite+martensite) in the microstructure originated from FBM, confirmed by quantifications through image analysis, EBSD and dilatometry transformation curves. The nucleation and growth of the austenite was affected by the previous microstructure, causing changes the morphology of the microstructure formed at the end of heating at lower intercritical temperature. The adoption of higher intercritical temperatures provided better homogeneity of the microstructure and, consequently, higher hole expansion capacity. The microstructural homogeneity was evaluated by nanoindentation, where it was verified that the lower hardness difference between the constituents of the microstructure given better results of hole expansion.